1998
DOI: 10.1111/j.1540-5915.1998.tb00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Priorities in Operations Management

Abstract: Identifying manufacturers' competitive priorities has long been considered a key element in manufacturing strategy research. However, relatively little effort has been devoted to measurement of these constructs in published research. In this study we develop scales for commonly accepted competitive priorities, cost importance, quality importance, delivery-time importance, and flexibility importance. We assess how well the scales capture the constructs that they represent using data collected from 114 manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
338
2
24

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(371 citation statements)
references
References 21 publications
7
338
2
24
Order By: Relevance
“…Hence consistent with the RBV, manufacturing capabilities have been posited and found to influence organizational performance (White, 1996;Ward et al, 1998;Flynn et al, 1999;Rosenzweig et al, 2003;Swink et al, 2005;Kim, 2006;Yu et al, 2014); specifically, how well an organization achieves its market and financial goals (Li et al, 2005). Market performance focusing on customer-oriented indicators such as growth in market share (Rosenzweig et al, 2003;Li et al, 2005;Swink et al, 2007) and financial performance referring to indicators that are assumed to reflect the fulfilment of the economic goal of the company such as profitability, return on investments (ROI), return on assets (ROA) and return on sales (ROS) (De Toni and Tonchia, 2001;Chen and Paulraj, 2004).…”
Section: Manufacturing Capabilities and Organizational Performancementioning
confidence: 71%
See 2 more Smart Citations
“…Hence consistent with the RBV, manufacturing capabilities have been posited and found to influence organizational performance (White, 1996;Ward et al, 1998;Flynn et al, 1999;Rosenzweig et al, 2003;Swink et al, 2005;Kim, 2006;Yu et al, 2014); specifically, how well an organization achieves its market and financial goals (Li et al, 2005). Market performance focusing on customer-oriented indicators such as growth in market share (Rosenzweig et al, 2003;Li et al, 2005;Swink et al, 2007) and financial performance referring to indicators that are assumed to reflect the fulfilment of the economic goal of the company such as profitability, return on investments (ROI), return on assets (ROA) and return on sales (ROS) (De Toni and Tonchia, 2001;Chen and Paulraj, 2004).…”
Section: Manufacturing Capabilities and Organizational Performancementioning
confidence: 71%
“…However, manufacturing capability refers to both process abilities as well as operational outcomes, which has brought some semantic differences and confusion over the term in the literature (Swink and Hegarty, 1998;Ward et al, 1998;Lau Antonio et al, 2007;Swink et al, 2007;Peng et al, 2008). The present study conceptualizes manufacturing capability as the actual (or realized) competitive ability (or strength) relative to primary competitors in the targeted market (Swink and Hegarty, 1998;Ho et al, 2002;Rosenzweig et al, 2003;Swink et al, 2007).…”
Section: Manufacturing Capabilities and Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Some conceptual studies suggested also innovativeness and service as additional priorities. Empirical research and strategy theories consistently stressed the four basic capabilities (Schmenner and Swink 1998;Ward, McCreery, Ritzman, and Sharma 1998). On the other hand, the operations performance factors for manufacturing firms are well established in the operations literature, which identifies cost, flexibility, quality, dependability, and speed as critical manufacturing competitive priorities (Vickeryet al 1997;Slack et al 2004).…”
Section: Operational Performancementioning
confidence: 99%
“…Capability dimensions mean: conformance quality, cost efficiency, delivery dependability, flexible responsiveness, new product development and new product introduction (Noble 1995;Ward et al 1995;Vickery et al 1997;Ittner and Larcker 1997b;Ward et al 1998;Ward andDuray 2000). Operations strategy should provide opportunities to help make core competencies and capabilities more tacit and untouchable.…”
Section: Operational Performancementioning
confidence: 99%